HYDROGEOLOGICAL ASSESSMENT OF THE CRETACEOUS STRATIGRAPHIC UNITS EXPOSED ALONG THE NORTH-EASTERN LIMB OF AZMAR ANTICLINORIUM, SULAIMANY, NE IRAQ - Amin, Dara (Iraqi Journal of Science, 2024)
Cretaceous stratigraphic water bearing units were evaluated hydrogeologically in combination with hydraulic parameters derived from single (productive) well test. The main recharge of water bearing units comes from percolation of precipitation. Generally all the tested wells taping water bearing units are productive wells and partially penetrating. The transmissivity values obtained by recovery test methods both by INFINITE EXTENT and AQTESOLVE 4.02 software programs reveal as high as double values calculated by constant pumping test methods, particularly for the Balambo aquifer, thus constant pumping test results were employed. While results for the Tanjero Formation are close and similar, therefore both methods were considered in calculating aquifer parameters. Some new hydrogeologic classification for those stratigraphic units was proposed and outlined under the section of hydrogeology. The groundwater flows from the NE limb of Azmar towards the east and north east directions. The hydraulic gradient is steeper within the Balambo aquifer, while it is gentler within the Tanjero aquitard. Drawdown of about 60m will be expected by the discharge of 432m3/day in the first 4 hours of pumping after which the Tanjero aquitard may approach the steady state and the drawdown may be minor. The groundwater storage in the Balambo aquifer indicates considerable volume that sustained water for long period in the region. Moreover, increasing drilling wells that associated with growing tourist activity and irrigation projects in the recent years, may affect most of the area within the Tanjero Formation, while this effect is limited within the Balambo aquifer system.